The Oldest Fauna Symbol-Words in the Mythopoetic Map of the Ukrainian Folk Song World (Linguostylistic Studies, 2021)
The article is devoted to the analysis of the oldest word-symbols, used to name animals: тур (bison), олень (єлень)(deer), лось (elk), вепр (wild pig), ведмідь (bear), віл (bull/bufallo), кінь (horse), змій (snake), павук (spider), and connected with the cosmogonic perceptions and beliefs of our ancestors. They are constituent parts of the mytho-poetic map of the world, reflected in the texts of folk songs. It has been specified that the notion “a folk poetic word-symbol” is a language symbol that has its individual sound form and reveals a constant associative connection with an object of the reality and a notion that is fixed in the mentality of the folklore bearers. A symbolic meaning has been considered as a derivational meaning of a word that appears as a result of strong associative connections. In the focus of the analysis is the fact that the names of wild animals – тур ‘bison’, олень (єлень) ‘deer’, лось ‘elk’, вепр ‘wild pig’, ведмідь ‘bear’ – combine such symbolic meanings as ‘strong physical strength’, ‘endurance’ and ‘space power’, that is why they are often endowed with supernatural extraordinary abilities. Thus, бик/віл (bull) and корова (cow), creators of the universe, are associated with the creation of the world. In the seasonal-ritual poetry the name коза (a female goat) conveys such symbolic meanings as ‘resurrection of an ancestor’, and ‘wealth/wellbeing’. Cosmogonic beliefs of our ancestors contributed to the linguistic descriptions of a диво-кінь (miracle horse), adding some extraordinary characteristics. A key lexeme кінь (horse) contains such semantic features as ‘space power’, ‘python’ – a medium between the world of the living and the dead, and ‘a transmitter of records’. Such fauna-symbols as ящур (lizard), змій (snake), and павук (spider) are associated with the lower layer of the world structure. Mythologemes ящур and змій(змія) reflect chthonic creatures, and actualize such symbolic meanings as ‘a  master of the underground and underwater kingdoms’, ‘magic healing power’, but their semantics in modern texts of folk songs is often ambiguous. The name павук (spider) has also become a myth-symbol in the folklore with the meanings ‘a weaver, a founder of the world’.
Keywords: word-symbol; fauna-symbol; symbolic meaning; folk song text